(untitled) (Materiali di Estetica. Terza serie, 2024)
Melancholia was already investigated in classical antiquity within a nosographic paradigm making ita disease of organic origin. Since the Renaissance, however, it is regarded as a disposition of mind, asad passion typical of those who excel in the arts and politics. Henri Bergson spoke of it as a pricethat human semiotic reason must pay to itself.